2016
DOI: 10.1161/circresaha.116.308807
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Accelerate Endothelial Senescence

Abstract: Rationale Proton pump inhibitors (PPIs) are popular drugs for gastroesophageal reflux, now available for long-term use without medical supervision. Recent reports suggest that PPI use is associated with cardiovascular, renal and neurological morbidity. Objective To study the long-term effect of PPIs on endothelial dysfunction and senescence and investigate the mechanism involved in PPI induced vascular dysfunction. Methods and Results Chronic exposure to PPIs impaired endothelial function and accelerated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 33 publications
0
103
0
4
Order By: Relevance
“…However, a subsequent study by the same authors in healthy volunteers and patients with CAD failed to validate this posited mechanism [6]. More recently, Yepuri et al reported that PPIs may accelerate senescence in human endothelial lysosomes by curtailing telomere length [7]; however, this mechanism requires further study.…”
Section: Ppis and Potential Cardiovascular Risk: A Mechanistic Undersmentioning
confidence: 99%
“…However, a subsequent study by the same authors in healthy volunteers and patients with CAD failed to validate this posited mechanism [6]. More recently, Yepuri et al reported that PPIs may accelerate senescence in human endothelial lysosomes by curtailing telomere length [7]; however, this mechanism requires further study.…”
Section: Ppis and Potential Cardiovascular Risk: A Mechanistic Undersmentioning
confidence: 99%
“…We read with great interest the study by Yepuri et al 1 on the effects of proton pump inhibitors (PPIs) on endothelial cells. The investigators exposed human microvascular endothelial cells to PPIs and observed reduced cell proliferation, a decrease in NO, and impaired proteostasis.…”
Section: Letter By Marlicz Et Al Regarding Article "Proton Pump Inhimentioning
confidence: 99%
“…However, there are several other compounds which display side effects likely associated toinduction of senescence. Very recently, accelerated endothelial senescence has been claimed as a potential mechanism to explain the cardiovascular, renal and neurological morbidity associated with proton pump inhibitors use [17]. The poor knowledge around effects on normal cells and potential side effects of senoltyics also deserve particular care.…”
Section: Hypothesis On the "Anti-senolytics Hell"mentioning
confidence: 99%